Determining the stage of development of a suspicious religious group through corpus analyses - Raymund T. Palayon; Richard Watson Todd; Sompatu Vungthong (International Review of Pragmatics, 2025)
Abstract Religious groups differ in the types of impact they have on society with most groups being beneficial, but some having detrimental effects, most noticeably destructive cults such as Peoples Temple led by Jim Jones. Social concerns about cults make it important to identify the stage of development of a suspicious religious group on a continuum from mainstream religion through sect and cult to destructive cult. In this paper, we applied the methods and findings of Palayon et al. (2021, 2022a) from a corpus linguistics perspective to the sermons of Apollo Quiboloy, the leader of the Kingdom Jesus Christ, as a suspicious religious group to identify its stage of religious development. From the findings, Apollo Quiboloy’s sermons display a philosophy and discourse characteristics being elaborative and persuasive associated with sects and some communication styles possibly associated with cults. This study may allow the stages of development of suspicious religious groups to be determined.
Keywords: Media, Religion, Digital Communication